Pengaruh Profitabilitas, Leverage, Likuiditas, Aktivitas, dan Manajemen Laba terhadap Audit Report Lag: (Studi Empiris pada Perusahaan Sektor Consumer Cyclicals yang terdaftar di Bursa Efek Indonesia Tahun 2019-2023) - Flavia Lunanda Wijaya; Wuri Septi Handayani (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2025)
This study aims to find out and analyze the influence of Profitability, Leverage, Liquidity, Activity, Profit Management on Audit report lag. In this study, it was carried out on companies in the Concumer Cyclicals Sector listed on the Indonesia Stock Exchange for the year 2019-2023. The sample determination method in this study uses the purposive sampling method and was obtained from 69 companies in the consumer cyclicals sector. The data analysis technique used in this study is multiple linear regression using SPSS version 22 software. Based on the results of the study, it can be concluded that profitability has a negative effect, leverage has a negative and significant effect, liquidity has a negative effect, activity has a positive effect, and profit management has no effect on audit report lag.